Color Aesthetic in the theatre show - Zhilwan Taher Bapir (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The research deals with the tagged (aesthetic color in theatrical presentation) analytical study, revealing the relationship of light color in terms of intellectual symbolic and semantic in the theatrical presentation, light and color are essential and effective elements in life and visual arts such as theater, which is in the structure of art performs aesthetic and scientific tasks within the theatrical presentation, scientific and artistic bases have psychological and aesthetic data. The research is divided into three chapters. The first chapter (methodological framework) deals with several points such as: problem of the study, importance of the study, objectives of the study and limits of study. The second chapter (theoretical framework) deals with the themes of light and color in the life of society, the dramatic effect of light and color, form and color, the effect of light and color in the stage show, the effect of lighting and color on the body of the actor, the effect of lighting and color on decoration, the effect lighting and color on fashion accessories, the effect of light and color on makeup. The third chapter deals with the analysis of three theatrical models. In the fourth chapter the study gained a number of results, the most important are the following: 1- The colors of the decoration give an indication of the event, place and time. 2- Light and color highlight the actor's body and visual connotations in the scenes of the stage show.